Mental health interventions in times of COVID-19: a scoping review - Moreira, Wanderson Carneiro (2020)
Objective: to map the evidence on mental health interventions implemented during the COVID-19 pandemic. Method: a scoping review carried out on the MEDLINE / PubMed, SCOPUS, Web Of Science, PsycINFO and Science Direct databases and on the medRxiv, bioRxiv and PsyArXiv preprint servers, using the descriptors “COVID-19”, “coronavirus infection”, “coronavirus”, “2019-nCoV”, “2019 novel coronavirus disease”, “SARS-CoV-2”, “health personnel”, “general public” and “mental health”. Results: eight articles were selected and categorized into: mental health interventions for the population, including mental health interventions for people with a suspected / confirmed diagnosis of COVID-19 and mental health interventions for health professionals. Conclusion: telemonitoring, virtual games and strategies focused on social support and muscle relaxation techniques, characterized as non-pharmacological and low-cost, which proved to be effective, need to be encouraged and included in care practices as interventions. mental health.